Poezja bez niepoezji, czyli meandry poezji czystej - Mazur, Elżbieta (Tematy i Konteksty, 2018)
The text is a review of the book by Gustaw Ostasz, entitled Śladami poezji czystej (Retracing Pure Poetry) and presenting considerations on the relationship between poetry and non-poetry. According to the reviewer the book stands out for its presentation of an important phenomenon in the modern lyric poetry, i.e. “pure poetry” understood as beauty, aesthetic ideal, and the Absolute. She also points out that, as an excellent supplement to the methodological considerations, the subse-quent chapters of the book present interpretations of major works of Polish 20th century literature, representing the concept of “pure poetry”.